Literature review on Big Data and Its Application Fields. Issue 4 (March 2019) - Fan, Xiani; Li, Zeping; Zhou, Li
Abstract: In recent years, due to information technology such as computer, Internet and the development of sensor technology, make modern life appeared "everything can be a digital" thinking, as a complex system test, test and condition monitoring of data series in growth, big data is becoming a hot research topic in the field of all kinds of industrial. This paper will start from the background of the era of big data, discuss the features of big data and its application in reality, and elaborate the trend of big data development from the perspective of data science, industry 4.0 and information physics system, and analyze the challenges of big data development.